2007
DOI: 10.3748/wjg.v13.i26.3554
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of gastric mucosa associated lymphoid tissue lymphoma

Abstract: Gastric mucosa associated lymphoid tissue (MALT) lymphoma has recently been incorporated into the World Health Organization (WHO) lymphoma classification, termed as extranodal marginal zone B-cell lymphoma of MALT-type. In about 90% of cases this lymphoma is associated with H pylori infection which has been clearly shown to play a causative role in lymphomagenesis. Although much knowledge has been gained in defining the clinical features, natural history, pathology, and molecular genetics of the disease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 123 publications
(146 reference statements)
0
47
0
8
Order By: Relevance
“…1,7 Ninety percent of patients with gastric MALToma were infected with H pylori. 8 Since the initial report on the regression of MALToma after H pylori eradication in 1993, there is a blooming interest in understanding the natural history and treatment for this uncommon disease.…”
Section: Maltoma Was First Described By Isaacson and Wright In 1983mentioning
confidence: 99%
“…1,7 Ninety percent of patients with gastric MALToma were infected with H pylori. 8 Since the initial report on the regression of MALToma after H pylori eradication in 1993, there is a blooming interest in understanding the natural history and treatment for this uncommon disease.…”
Section: Maltoma Was First Described By Isaacson and Wright In 1983mentioning
confidence: 99%
“…33 Most chemotherapy combinations report response rates of over 90% and purine analogue-based therapy ap- pears to have more efficacy but also more toxicity than alkylator-based therapy. 34 In fact, one publication indicated cases with t(11;18) tended to be poorly responsive to oral alkylator therapy. 35 Regression of established disease can be quite slow after H pylori eradication therapy, with some reports indicating a full year before complete remission was established.…”
Section: Gastric Malt Lymphomasmentioning
confidence: 99%
“…This MALT provides the necessary background in which gastric lymphomas can develop. Even though primary gastric lymphoma accounts for less than 3% of all nonHodgkin's lymphomas (NHL) and about 7% of all gastric neoplasms, the stomach is the most common site of extranodal NHL, with most gastric lymphomas being of B-cell origin [57,58] (Fig. 2).…”
Section: H Pylori and Malt Lymphomamentioning
confidence: 99%
“…CagA-positive strains of H. pylori have been especially associated with this more aggressive form of gastric lymphoma [73]. Since high-grade and low-grade forms of gastric lymphoma can occur simultaneously, H. pylori infection should always be sought and the infection eradicated to minimize low-grade tumor relapse [58], even when additional oncological therapy is given. Surprisingly, it may still be prudent to eradicate H. pylori as the initial therapy in MALT lymphomas that are negative for H. pylori , as some studies have shown successful regression of tumors without any further therapy [74].…”
Section: H Pylori and Malt Lymphomamentioning
confidence: 99%
See 1 more Smart Citation